Post-harvest performance of 'Abate Fetel' pears grown in Argentina in relation to harvest time - Calvo, Gabriela; Candan, Ana Paula; Gomila, Teofilo (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010